Effects of molybdenum nanoparticles on lead-free tin-based solder / Md. Arafat Mahmood - Md. Arafat, Mahmood (2012)
Recent environmental concern led to worldwide legislation banning the use of lead (Pb) containing solders in microelectronic devices. Near eutectic Sn-Ag-Cu solders are considered as replacement for traditional Pb-Sn solders. But Sn-Ag-Cu solder alloys can not guarantee the required performance in wide ranging semiconductor products. The aim of this work is to develop tin-based nanocomposite solder with improved high temperature stability with respect to microstructure and properties. In this study, Mo nanoparticles were used as a reinforcing material into the Sn-3.8Ag- 0.7Cu (SAC) solder. The Mo nanoparticles were characterized by transmission electron microscopy (TEM) and X-ray diffractometer (XRD). The composite solder paste was prepared by manually mixing of Mo nanoparticles into the SAC solder paste. The melting behavior of the solder paste was determined by differential scanning calorimetry (DSC). The as-prepared solder paste was placed on polycrystalline Cu substrate and reflowed at 250ºC for 45 seconds. After reflow, elemental compositions of the nanocomposite solders were analyzed by inductively coupled plasma-optical emission spectrometer (ICP-OES). The microstructural investigations, spreading rate and wetting angle measurement were carried out on the solders after first reflow. After that one set of samples subjected to multiple reflow up to six times and another set of samples were put for high temperature aging up to 1008h at 100º-175ºC. Microstructural investigations were performed at the solder/substrate interface using conventional scanning electron microscopy (SEM), high resolution field emission scanning electron microscopy (FESEM) and energy dispersive X-ray (EDX). To evaluate the solder/substrate interaction in the liquid state in presence of Mo nanoparticles, Cu wire (250 μm in diameter) was dipped into the liquid composite solder at 250ºC up to 15 min. After that, the solder-substrate reaction couple was taken out from the molten solder and examined thoroughly by optical microscopy, SEM, FESEM, and EDX. Results reveal that after reflow only a fraction of Mo nanoparticles retain inside the solder matrix. The spreading rate decreased and wetting angle is increased with the addition of Mo nanoparticles to the SAC solder. It is found that Mo nanoparticles are effective in suppressing the growth of total IMC layer thickness and scallop diameter during reflow and high temperature aging. With the addition of Mo nanoparticles, the diffusion coefficient is decreased but the activation energy of the IMC scallop growth remains unchanged. The dissolution of Cu substrate and IMC formation are decreased in presence of Mo nanoparticles. From this present research, it was found that Mo nanoparticles do not dissolve or react with the solder during reflow and high temperature aging. The retardation of IMC thickness and scallop diameter is due to the discrete particle effect of Mo nanoparticles. The intact, discrete nanoparticles, by absorbing preferentially at the interface, hinder the diffusion flux of the substrate and thereby suppress the IMC growth. The retardation of total IMC layer with the addition of Mo nanoparticles improves the reliability of the solder joint.